2021
DOI: 10.1128/mra.00471-21
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Genome Sequencing of Leishmania infantum chagasi Isolates from Honduras and Brazil

Abstract: This work reports on the whole-genome sequencing of Leishmania infantum chagasi from Honduras (Central America) and Brazil (South America).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 10 publications
1
24
0
1
Order By: Relevance
“…Our results represent the first genomic analysis performed in Latin America on whole-genome sequences of L. (L.) infantum chagasi from Honduras (Central America), the same parasite from Brazil (South America), and sequences of L. (L.) infantum (Europe) and L. (L.) donovani (India). The three parasite genomes revealed high genomic identity (~99%) [except L. (L.) donovani ], although previously molecular clock comparisons of the DNA polymerase alpha subunit gene (a highly conserved genomic region related to the evolutionary process of leishmanine parasites [ 26 ]) among these parasites indicated that the Honduran parasite was significantly older (382,800 ya ) than the Brazilian parasite (143,300 ya ), L. (L.) donovani (33,776 ya ), or L. (L.) infantum (13,000 ya ) [ 18 ]. Moreover, the Honduran parasite was found to have a single structural variation (and perhaps also a single functional variation) on chromosome 17 ( Figure 2 ), as well as the highest frequency of genomic SNPs (more than twice that of the Brazilian parasite) ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our results represent the first genomic analysis performed in Latin America on whole-genome sequences of L. (L.) infantum chagasi from Honduras (Central America), the same parasite from Brazil (South America), and sequences of L. (L.) infantum (Europe) and L. (L.) donovani (India). The three parasite genomes revealed high genomic identity (~99%) [except L. (L.) donovani ], although previously molecular clock comparisons of the DNA polymerase alpha subunit gene (a highly conserved genomic region related to the evolutionary process of leishmanine parasites [ 26 ]) among these parasites indicated that the Honduran parasite was significantly older (382,800 ya ) than the Brazilian parasite (143,300 ya ), L. (L.) donovani (33,776 ya ), or L. (L.) infantum (13,000 ya ) [ 18 ]. Moreover, the Honduran parasite was found to have a single structural variation (and perhaps also a single functional variation) on chromosome 17 ( Figure 2 ), as well as the highest frequency of genomic SNPs (more than twice that of the Brazilian parasite) ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our results clearly suggest that the low genomic heterogeneity of L. (L.) infantum chagasi reflects the parasite’s low genomic plasticity (due to its older ancestry) much more than its recent introduction into the New World. Likewise, another species belonging to the L. ( Leishmania ) subgenus [ L. (L.) amazonensis ], an ancient species of this subgenus that was identified in previous work [ 18 ]), evidenced low genomic plasticity in relation to other species of later ancestry in the subgenus L. (Viannia) [such as L. (V.) braziliensis and L. (V.) panamensis ], suggesting that low plasticity may be a genomic characteristic of the subgenus L. ( Leishmania ) [ 28 , 29 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Da pouca literatura existente em relação à caracterização do agente etiológico da forma cutânea não ulcerada e visceral em Honduras, em 1991, Ponce e colaboradores caracterizaram 4 isolados de pacientes com LCNU e 2 com LV de Honduras, por meio de análise de isoenzimas e anticorpos monoclonais de pacientes de Honduras, esses isolados foram caracterizados por eletroforese de isoenzimas, anticorpos monoclonais e DNA-RAPD, como L. (L.) infantum chagasi(NOYES et al, 1997). Assim os autores, Ponce e Noyes, sugerem que o agente etiológico que causa as lesões cutâneas não ulceradas e a leishmaniose visceral em Honduras é L.(L.) infantum chagasi, dado que foi confirmando em nosso estudo, uma vez que a caracterização de 100% dos isolados de LV e das lesões cutâneas dos pacientes com LCNU mostrou que o agente etiológico é L. (L.) infantum chagasi SILVEIRA et al, 2021)…”
unclassified